Synthesis, characterization, and in silico and in vivo profiling of selective cyclo-oxygenase-2 inhibitors of indazole–indolinone derivatives with anti-inflammatory and analgesic potency - Alkubaysi, Sultan Ibrahim; Mantargi, Mohammad Jaffar Sadiq; Almalki, Faisal Ateeq; Alqahtani, Alaa Mohammad; Baryyan, Alaa Omar; Tayeb, Saeed Mohammad; Muathen, Hussni Ahmad (Frontiers in Pharmacology, 2026)
BackgroundThe intensive use of non-steroidal anti-inflammatory and analgesic drugs (NSAIDS) worldwide poses a challenge to scientists because of the adverse side effects. This article aims to synthesize a novel group of 1-aminoindazole-isatin Schiff base compounds considering their potency as analgesic and anti-inflammatory agents.MethodsThe synthesis of novel agents involved reflux condensation of isatin derivatives (5 mmol) and 1-aminoindazole (5 mmol) in ethanol for 2 h, which were then characterized for their structural integrity. In silico evaluation using PyRx, BIOVIA Discovery Studio, and GROMACS was performed to determine the affinity of the specific receptors and compare them with the results gained by use of standard diclofenac before preclinical evaluation using albino mice (analgesic activity) and rats (anti-inflammatory activity). The preclinical analgesic potency was analyzed via Eddy’s hot plate and tail-pin methods, whereas, the anti-inflammatory potency was analyzed through carrageenan-induced paw edema against diclofenac as the standard agent.ResultsA high percentage yield of the reactions was determined (≈80%); the IR, NMR, and mass spectra showed the compounds to be stable with no shifts, justifying the accuracy of the procedure employed. The molecular docking of the ligands with two different crystal structures of proteins of interest, i.e., COX-1 and COX-2, yielded stable and the lowest binding energies, i.e., −9.6 kcal/mol for AB 12 and – 7.1 kcal/mol for diclofenac. Through molecular dynamic simulations employing GROMACS for a time period of 50 ns, AB 12 and diclofenac also yielded a thermodynamically stable and structurally folded protein and ligand complex, showing an average of 0–3 (AB 12) and 0–5 (diclofenac) hydrogen bonds with the least system fluctuations and atom deviations; furthermore, the potential energy of the complete system was stabilized at an average point of – 685,000 kj/mol for both molecules. The preclinical results showed a significant value for the ligand AB 12 (p ≤ 0.01) against the diseased control group.DiscussionThe ligand AB 12, AB 14 and AB 15 is exceptional as an analgesic and anti-inflammatory agent. AB 12 further showed stable hydrogen bonds with protein COX-2 for 50 ns in comparison with diclofenac. Based on this study, these molecules can be considered best for future studies regarding the toxicological profile.